An Approach to Report Writing in the World of Work - Keedwell, Andy (Armenian Folia Anglistika, 2005)
The British Council has elaborated certain materials aimed at developing the writing skills, especially report writing, of the students who have already reached upper-intermediate level of English competence. The article presents the process of the use of the abovementioned materials among Armenian junior diplomats and other people working in other fields. It further analyzes the methods that will help overcome linguistic difficulties that might arise while writing a report.